2022
DOI: 10.1177/10711007221096674
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Percutaneous Achilles Repair Compared With Endoscopic Flexor Hallucis Longus Tendon Transfer to Treat Achilles Tendon Ruptures

Abstract: Background: Both percutaneous and endoscopically assisted methods are reported to produce good results in the surgical management of acute Achilles tendon ruptures. The aim of this retrospective study was to compare between a percutaneous method and a recently described isolated endoscopically assisted flexor hallucis longus (FHL) transfer method as surgical means of management in patients with acute Achilles tendon ruptures. Methods: One hundred seventeen patients were included in the current study and divide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…The current study allocated the same beneits to endoscopic FHL transfer patients as other surgical treatments. However, prospectively collected data support the assumption that this treatment will provide at least similar beneits to the other surgical treatments [1,6]. For example, the Achilles Tendon Total Rupture Score (ATRS) was higher, at a value of 95 ± 4.26, for endoscopic FHL transfer in the study by Batista et al [6] than the values reported for open surgery by Olsson et al [46], with ATRS value of 82 ± 20 and EQ-5D values of 0.91 ± 0.17.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The current study allocated the same beneits to endoscopic FHL transfer patients as other surgical treatments. However, prospectively collected data support the assumption that this treatment will provide at least similar beneits to the other surgical treatments [1,6]. For example, the Achilles Tendon Total Rupture Score (ATRS) was higher, at a value of 95 ± 4.26, for endoscopic FHL transfer in the study by Batista et al [6] than the values reported for open surgery by Olsson et al [46], with ATRS value of 82 ± 20 and EQ-5D values of 0.91 ± 0.17.…”
Section: Discussionmentioning
confidence: 93%
“…Vertical lines represent WTP thresholds. QALY quality-adjusted life-years the assumption of comparable patient-reported outcomes between these treatments, speciically between open and MIS [2] and between MIS and endoscopic FHL transfers [1].…”
Section: Open Surgerymentioning
confidence: 99%
See 1 more Smart Citation